2014
DOI: 10.1002/2013jb010116
|View full text |Cite
|
Sign up to set email alerts
|

Source parameter scaling and radiation efficiency of microearthquakes along the Irpinia fault zone in southern Apennines, Italy

Abstract: We analyzed the P and S wave displacement spectra of 717 microearthquakes in the moment range 4 × 10 9 À 2 × 10 14 N m recorded at the dense networks operating in southern Apennines (Italy) and deployed along the 1980 M s 6.9 Irpinia earthquake fault zone. Source, attenuation, and site parameters are estimated by using a parametric modeling approach, which is combined with a multistep, nonlinear inversion strategy. We found that in the analyzed frequency band, an attenuation model with constant Q has to be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 58 publications
10
72
0
1
Order By: Relevance
“…The seismic radiation efficiency η SW , related to the high γ , resulted for most of the events smaller than the 0.3 threshold suggested by Beeler et al [], which indicates positive overshoot. These findings agree with the η SW observed by Zollo et al [] when analyzing the natural microseismicity in Southern Italy, a region where the crust is considered highly fractured and partially or completely saturated with fluids. Regarding the fluids at TG, both the original works of Stark [] and the recent studies of Martínez‐Garzón et al [2013, ] and Jeanne et al [] emphasize that their injection into the reservoir induces seismicity by both thermal and/or poroelastic stress changes.…”
Section: Discussionsupporting
confidence: 92%
“…The seismic radiation efficiency η SW , related to the high γ , resulted for most of the events smaller than the 0.3 threshold suggested by Beeler et al [], which indicates positive overshoot. These findings agree with the η SW observed by Zollo et al [] when analyzing the natural microseismicity in Southern Italy, a region where the crust is considered highly fractured and partially or completely saturated with fluids. Regarding the fluids at TG, both the original works of Stark [] and the recent studies of Martínez‐Garzón et al [2013, ] and Jeanne et al [] emphasize that their injection into the reservoir induces seismicity by both thermal and/or poroelastic stress changes.…”
Section: Discussionsupporting
confidence: 92%
“…This value is somehow lower than that observed by Viegas and Hutchings [] who used the empirical Green's function technique and NetMoment methods to investigate the source properties of seismicity in the same Prati‐9 system and obtained the median stress drop of 28 MPa. In contrast, Convertito et al [] reported low stress drop values of 2 MPa at The Geysers using the iterative multistep inversion of source parameters [ Zollo et al , ]. The seismicity refined with the spectral ratio technique is self‐similar and does not display any signatures of scaling breakdown, which was visible in the source parameters calculated using the spectral fitting method only (gray points in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…For the same investigated area, recent measurements of the S ‐to‐ P quality factor ratio Q S / Q P have been made based on the spectral analysis of micro‐earthquake records, resulting in a median crustal Q S / Q P = 1.2, and 80% confidence bounds (0.9; 1.6) [ Stabile et al ., ; Zollo et al ., ]. In rock volumes saturated with a low‐viscosity fluid (e.g., water and oil), laboratory measurements at ultrasonic frequencies using a pulse amplitude technique found Q P < Q S for partially saturated rock samples [ Toksoz et al ., ].…”
Section: Discussionmentioning
confidence: 99%